Transformasi Ekonomi: Membangun Kesejahteraan Masyarakat Melalui Pendekatan Ekonomi Hijau - Sugianto Sugianto; Mubarok El Alimi; Aprielle Ego Pasha (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
This research aims to investigate the potential and strategies for accelerating economic transformation towards social welfare through a green economy approach. The green economy approach has been recognized as an effective way to integrate economic, environmental and social sustainability in economic development. Through descriptive analysis, this research identifies opportunities, challenges and policies needed to encourage sustainable and inclusive economic growth. The findings from this research will provide valuable insights for policy makers, practitioners and academics in designing and implementing policies that support sustainable economic transformation by considering opportunities and challenges in generating community prosperity with sustainable economic growth.